Pengaruh Model Flipped Classroom Berbantuan Genially terhadap Kemampuan Pemecahan Masalah dan Self-Efficacy Matematis Siswa - Stephanus, Johannes R. (Al-Alam: Islamic Science Education Journal, 2025)
This quasi-experimental study investigates the effectiveness of implementing the Flipped Classroom model assisted by Genially interactive media in improving junior high school students' Mathematical Problem-Solving Ability (MPSA) and self-efficacy. The research design applied was a nonequivalent control group design. The subjects were from the entire population of eighth-grade students at Haruru Christian Middle School for the 2024/2025 academic year, with the sample selected using purposive sampling. The sample consisted of class VIII1 (23 students) as the experimental group and class VIII2 (25 students) as the control group. Data was collected using two instruments: an MPSA essay test (5 questions, α=0.81) and a self-efficacy questionnaire (20 statements, α=0.87). Data analysis was performed using Multivariate Analysis of Variance (MANOVA). The findings revealed a significant simultaneous difference between the experimental and control groups on MPSA and self-efficacy (Pillai's Trace = 0.381, F = 18.752, p < .001). Follow-up tests indicated that significant differences occurred in both MPSA (F=18.329, p<.001) and self-efficacy (F=15.874, p<.001), with the experimental group achieving higher mean scores on both variables. Based on these results, it is concluded that the Genially-assisted Flipped Classroom model is effective in significantly enhancing students' mathematical problem-solving ability and self-efficacy. The implication of this finding advocates for the integration of interactive technology in mathematics learning to develop skills relevant to the 21st century.